A rod conformation of the Pyrococcus furiosus Rad50 coiled coil. Issue 2 (25th September 2020) - Soh, Young‐Min; Basquin, Jerome; Gruber, Stephan
Abstract: The Rad50‐Mre11 nuclease complex plays a vital role in DNA repair in all domains of life. It recognizes and processes DNA double‐strand breaks. Rad50 proteins fold into an extended structure with a 20 to 60 nm long coiled coil connecting a globular ABC ATPase domain with a zinc hook dimerization domain. A published structure of an archaeal Rad50 zinc hook shows coiled coils pointing away from each other. Here we present the crystal structure of an alternate conformation displaying co‐aligned coiled coils. Archaeal Rad50 may thus switch between rod‐shaped and ring‐like conformations as recently proposed for a bacterial homolog.